Tribological investigation of Zamak alloys reinforced with alumina (Al2O3) and fly ash. (3rd May 2016) - Almomani, Mohammed; Hayajneh, Mohammed T.; Draidi, Majd
ABSTRACT: In this study, zinc aluminum alloy (Zamak) (ZA-27) composites reinforced by different weight fractions of fly ash, alumina (Al2 O3 ), or both particles were produced using compo-casting technique. The composites were subjected to hardness and wear tests. The hardness of the composites increases with increase of the weight fractions of reinforcements. In wear test, the composites were examined under dry sliding conditions using pin on disc apparatus. The wear results revealed that the wear resistance increases with increase of the weight fractions of reinforcements. However, the effect of fly ash particles on the wear resistance of the produced composites is more statistically significant than the effect of Al2 O3 particles. The morphology of the composites was examined using scanning electron microscopy (SEM) after the test. The SEM images revealed the existence of adhesion and delamination wear mechanism.